Association of 8-isoprostanes level and renal impairment in spontaneously hypertensive rats - Wahab, Nor Akmal (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Prolonged uncontroled hypertension is known to cause renal impairment . The precise mechanism by which raised systemic blood pressure leads to renal impairment is unclear. Free radicals have been implicated in cell damage and hypert~nsive has been shown to have higher level of plasma lipid peroxidation end product malondialdehyde (N.IDA) than normal individuals . This study · aims to ascertain the levels ofMDA in spontaneously hyp,ertensive rats (SHR) and determine the age at which changes in the levels ofMDA and renal impairment begin to occur in SHR. Sixty-six r;nale SHR, aged 8 weeks~- were divided into eleven groups. A similar number of male Wistar Kyoto rats (WKY) were also similarly divided to act as parallel controls. Body weight , systemic blood pressure and plasma ~A were measured every four \¥eeks starting from the age of 8th weeks until the age of 48th week. Plasma MDA was measured using High Performance Liquid Chromatography (HPLC). Every four weeks, six rats per group were anaesthetized for measurement of Glomerular Filtration Rate (GFR), using standard clearance procedures, to assess the renal function. Mean body weight of SHR was consistently lower than that of WKY rats from the·age of 12 weeks onwards (p < 0.05). Blood pressure, on the other hand, was significantly higher in the SHR when compared to that in age-matched WKY rats from the age of8 weeks onwards (p < 0.05). Interestingly, plasma :MDA levels was higher in the SHR than in the controls only from the age of 12 weeks, reaching statistical significance by the age of24, 44 and 48 weeks. GFR was lower iii 'SFIR from The age of24 weeks onwards (p .. <0.05). It appears that there is an age-related decline in GFR in SHR, implying renal impairment , particularly from the age of 24 weeks onwards when compared to WKY rats but plasma :MD A levels was higher in the SHR than in the controls from the age of 12 weeks. It is unclear if the decrease in GFR is a result of the raised levels ofMDA, but it appears that renal impairment occurs subsequent to changes in plasma :MDA levels. Clearly, more studies are needed to ascertain the relationship between the changes in GFR and :MDA in hypertension.